Asian Martial Art Exhibitions at the Swiss Castle of Morges - Bialokur, Nicolae Gothard (Revista de Artes Marciales Asiáticas, 2012)
This article reports on two unique cultural exhibitions (2005 and 2007) held in Morges, Switzerland. The main theme for these exhibitions was Asian martial arts with a focus on those from Japan, including presentations by notable masters in aikido, karate, judo, kyudo, iaido, kenjutsu, jodo, juttejutsu, kusarigamajutsu, naginatajutsu, tameshigiri, and kendo. On exhibit were artifacts from Morges Castle museum collections as well as numerous ancient objects borrowed specifically for these exhibitions from other Swiss museums and private collections. There was also a lecture on Japanese sword collecting and care, and presentations of Japanese dance, flower arranging (ikebana), the art of tea (châ no yu, châdo), paper folding (origami), traditional kimono dress, and detailed demonstrations on the manufacture of bladed weapons. Text and photography were arranged to record these events for this article, showing how excellent organization and cooperation can introduce high-quality martial traditions to the public.